Predictors of Longitudinal Changes in Pulmonary Function among Swine Confinement Workers - Shelley P Kirychuk; Ambikaipakan Senthilselvan; James A Dosman; Chen Zhou; Ernie M Barber; Chuck S Rhodes; Tom S Hurst (Canadian Respiratory Journal)
OBJECTIVE: To determine predictors of longitudinal changes in pulmonary function in swine confinement workers.